Traumatic rupture of an intracranial dermoid cyst: A case report - Das, Uddalok; Pandit, Narayan (Eastern Journal of Medical Sciences, 2021)
Intracranial dermoid cyst is a very rare primary intracranial tumor accounting for <0.5% of intracranial masses. They are usually congenital and benign. Rupture of intracranial dermoid may occur spontaneously or with trivial trauma. Most cases of rupture are spontaneous. There are very few reported cases of traumatic rupture of intracranial dermoid cysts in world medical literature. The presentation can range from headache to signs of meningeal irritation and focal neurological deficit. Computed tomography (CT) and magnetic resonance imaging (MRI) of the brain is of paramount importance for early diagnosis and prompt treatment planning which can reduce both morbidity and mortality. The following case report gives an account of a 49-year-old female who presented with complaints of headache after an episode of fall. She was examined and no neurological deficit was found. Examination of the neurological system was within normal limits. She underwent a CT and MRI of the brain and was subsequently diagnosed as traumatic rupture of dermoid cyst based on the findings. She was treated with high-dose steroids until resolution of her symptoms and then discharged with the advice of regular follow-up. This case report highlights the role of CT and MRI in early diagnosis and treatment planning of patients with ruptured dermoid cysts which leads to a decrease in mortality and morbidity and also the ability of the same to rule out other more sinister causes of headache in patients.